2012
DOI: 10.1007/s10995-012-1025-8
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors for Accelerated Growth in Childhood: A Systematic Review

Abstract: Several studies have shown that accelerated growth in the postnatal period is critical for the development of chronic diseases. The term catch-up has been used for the accelerated growth of children who have suffered some sort of restriction of nutrition or oxygen supply. However, accelerated growth has been observed among children who have an appropriate birth weight for their gestational age (AGA) and with no apparent morbidity. Therefore, this systematic review was carried out on the associated factors of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
0
33
0
2
Order By: Relevance
“…Primiparity has consistently been reported to be associated with rapid infant growth (Ong et al 2002, Karaolis-Danckert et al 2009, Chrestani et al 2013). We did not adjust for parity in our analysis, as parity is an important predictor of chemical levels as the maternal level of persistent chemicals declines with parity and breast-feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primiparity has consistently been reported to be associated with rapid infant growth (Ong et al 2002, Karaolis-Danckert et al 2009, Chrestani et al 2013). We did not adjust for parity in our analysis, as parity is an important predictor of chemical levels as the maternal level of persistent chemicals declines with parity and breast-feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Catch-up growth was defined as a positive change in SDS (DSDS) R0.67 S.D. for weight and height respectively (Ong et al 2000, Chrestani et al 2013, and catch-down growth was defined as DSDS %K0.67 S.D. (Ong et al 2004).…”
Section: Clinical Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current analysis revealed a strong association between birth weight and the anthropometric nutritional status of children, with similar results in previous studies, such as studies based on municipal or state population data (Jesus, Castelão, Vieira, Gomes, & Vieira, 2014;Figueiroa et al, 2012;Rissin et al, 2011) and in populations marked by social inequity Lang et al, 2011;Silveira et al, 2010). This association, verified for several anthropometric indexes (Figueiroa et al, 2012;Figueroa Pedraza et al, 2013;Horta et al, 2013;Jesus et al, 2014;Lang et al, 2011;Rissin et al, 2011;Silveira et al, 2010), shows two perspectives: i) children with low birth weight, regardless of compensatory growth in the first three months of life, continue to have weigh rates below those of children with adequate birth weight, contributing to increased vulnerability to infectious processes and other negative postnatal factors, which are added to the prenatal growth programming (Motta, Silva, Araújo, Lira, & Lima, 2005); ii) low birth weight may result in adaptation mechanisms such as catch-up growth and hormonal disorders that might predispose the child to the development of overweight / obesity (Chrestani, Santos, Horta, Dumith, & Dode, 2013;Motta el al., 2005;Rossi & Vasconcelos, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal growth has been shown to be inversely associated with postnatal growth, with babies born smaller experiencing higher growth during infancy compared with larger babies. 21,24,25 It has been suggested that babies who experience growth restriction in utero and therefore are born small compensate by growing rapidly in early infancy, and that this mismatch between prenatal and postnatal growth may elevate risks of obesity and other chronic diseases. [26][27][28] If this is the case, there could be trade-offs between the short-term benefits of 'catch-up' growth and chronic disease risk in the longer-term.…”
Section: Introductionmentioning
confidence: 99%